Impact of class configuration on political participation: Evidence from Gowa Regency, Indonesia - Syamsu, Suhardiman; Ansar, Muhammad Chaeroel; Nurlinah, (Frontiers in Political Science, 2025)
This study examines political participation in rural areas, emphasizing class configurations shaped by agricultural practices and socio-economic structures. A household survey of 261 respondents was conducted and regression analysis was applied to assess rural class configuration and political participation, using Gowa Regency in South Sulawesi, Indonesia, as the focal area due to its agricultural importance and class complexity. The findings identify six class configurations—Fully-Proletariat-Farmer, Proletariat-Farmer, Semi-Proletariat-Farmer, Petty Commodity Producer, Capitalist-Farmer, and Capitalist-Landlord—based on property ownership, land relations, and employment. The findings demonstrate that landowners and capitalist farmers have greater access to formal political processes, whereas small-scale farmers and landless laborers exhibit lower levels of participation. However, informal participation, such as participation in village meetings, is more prevalent among economically vulnerable groups. Regression analysis reveals that class configuration positively correlates with formal and informal political participation, suggesting that improving socio-economic conditions can enhance civic participation. Education, age, and employment in non-agricultural sectors significantly increase political participation. To strengthen rural political participation, policies should focus on equitable land distribution, expanded political education, inclusive governance, and gender-responsive initiatives. Economic diversification should also be encouraged to reduce dependence on agriculture and increase political participation. Future research should explore long-term class transitions and their implications for democratic participation in rural communities. These efforts can contribute to a more inclusive and participatory rural governance structure.